Longitudinal Associations Between Changes in Cigarette Smoking and Alcohol Use, Eating Behavior, Perceived Stress, and Self-Rated Health in a Cohort of Low-Income Black Adults. Issue 1 (10th May 2021) - Bloom, Erika Litvin; Bogart, Andy; Dubowitz, Tamara; Collins, Rebecca L; Ghosh-Dastidar, Bonnie; Gary-Webb, Tiffany L; Troxel, Wendy
Abstract: Background: Black adults in the U.S. experience significant health disparities related to tobacco use and obesity. Conducting observational studies of the associations between smoking and other health behaviors and indicators among Black adults may contribute to the development of tailored interventions. Purpose: We examined associations between change in cigarette smoking and alcohol use, body mass index, eating behavior, perceived stress, and self-rated health in a cohort of Black adults who resided in low-income urban neighborhoods and participated in an ongoing longitudinal study. Methods: Interviews were conducted in 2011, 2014, and 2018; participants ( N = 904) provided at least two waves of data. We fit linear and logistic mixed-effects models to evaluate how changes in smoking status from the previous wave to the subsequent wave were related to each outcome at that subsequent wave. Results: Compared to repeated smoking (smoking at previous and subsequent wave), repeated nonsmoking (nonsmoking at previous and subsequent wave) was associated with greater likelihood of recent dieting (OR = 1.59, 95% CI [1.13, 2.23], p = .007) and future intention (OR = 2.19, 95% CI [1.61, 2.98], p < .001) and self-efficacy (OR = 1.64, 95% CI [1.21, 2.23], p = .002) to eat low calorie foods, and greater odds of excellent or very good self-rated health (OR = 2.47, 95% CI [1.53, 3.99], p < .001). Transitioning from smoking to nonsmoking was associated with greater self-efficacy to eat low calorie foods (OR = 1.89, 95% CI [1.1, 3.26], p = .021), and lower perceived stress ( β = −0.69, 95% CI [−1.34, −0.05], p = .036). Conclusions: We found significant longitudinal associations between smoking behavior and eating behavior, perceived stress, and self-rated health. These findings have implications for the development of multiple behavior change programs and community-level interventions and policies. Abstract : Among low-income Black adults living in two urban neighborhoods, we found that cigarette smoking was related to stress, perception of general health, and eating behavior.